A Prospective Study of Serum IL-15, TNF-α, and YKL-40 as Predictors of Knee Osteoarthritis Progression: Serum IL-15, TNF-α, and YKL-40 in Osteoarthritis - Wu, Zungui; Liu, Yu; Xie, Peigeng; Xiong, Chunxiang (Journal of Medical Biochemistry, 2026)
-
Keywords: Osteoarthritis; Biomarkers; Prognosis; Cytokines; IL-15; TNF-α; YKL-40; Inflammation.